Effects of diuron and two of its metabolites in biochemical markers and behavior of zebrafish larvae - Sales, Bianca Camargo Penteado; Pereira, Lílian Cristina; Quintaneiro, Carla; Soares, Amadeu Mortágua Velho da Maia; Monteiro, Marta Sofia (Springer Nature, 2024)
Diuron (3-(3,4-dichlorophenyl)-1,1-dimethylurea) is an herbicide used in many crops, including sugar cane cultivation. It is commonly found in aquatic ecosystem and is of high concern due to its ability to persist in the environment. Diuron metabolites include DCA (3,4-dichloroaniline) and DCPMU (3-(3,4-dichlorophenyl-1-methylurea). The objective of this study was to evaluate the effects of diuron and two of its metabolites in zebrafish (Danio rerio) developing embryos, from biochemical to individual level. Activities of the enzymes acetylcholinesterase (AChE), catalase (CAT), glutathione-S-transferase (GST), and lactate dehydrogenase (LDH) and the levels of lipid peroxidation (LPO), swimming activity, and body length were investigated after an exposure of 120 h, and the heart rate was determined after 48 h of exposure. The range of concentrations tested was 0.003–3.000 mg/L diuron, 0.020–1.500 mg/L DCA, and 0.020–2.100 mg/L DCPMU. Results showed that AChE activity was inhibited by diuron (3.000 mg/L) and DCPMU (0.326, 0.828 mg/L). However, the swimming activity of fish larvae exposed to diuron or its metabolites was not affected. The CAT was induced by DCPMU, and GST was induced by diuron. This suggests that CAT is acting to cope with oxidative stress induced by DCPMU and GST might have a role in the detoxification of diuron. In addition, larvae exposed to DCA (0.633 and 1.500 mg/L) had a reduction in their length, and larvae exposed to diuron (0.754 and 3.000 mg/L) and DCA (0.267, 0.633, and 1.500 mg/L) presented bradycardia, suggesting cardiotoxicity. Overall, results indicate that diuron, DCA, or DCPMU induces adverse effects during the early phases of zebrafish development, such as the impairment of neurotransmission and cardiovascular function and alterations in antioxidant enzymes and growth. Diuron appeared as more toxic than its metabolites since the lowest LOEC (0.012 mg/L) and higher integrated biomarker response (IBR) values were obtained with exposure to this herbicide. Furthermore, as it is fast degraded into DCA and DCPMU, which also affected the zebrafish developing embryos at environmentally relevant concentrations, its use might be of concern in ecosystems that receive agriculture runoff due to their potential adverse effects to aquatic biota.